Evaluation of Bioactive Compounds and Mineral Composition in Thai-Variety Amaranths - Chunthawodtiporn, Jareerat; Manochai, Benya; Santhi, Kornkanok; Pornwongthong, Peerapong (Applied Science and Engineering Progress, 2023)
Amaranth is one of the high nutrient vegetables with high proteins, vitamins, and mineral contents. However, the accumulated pigments and nutrients may change by plant growth stages. Therefore, this study explored the phytonutrients and mineral composition in three amaranth varieties with five harvesting stages. The results revealed that plant pigments were highest accumulated at the reproductive stage with anthocyanin and β-carotene contents of 0.82 and 141.21 mg/g fresh weight (FW), respectively. Contrastingly, vitamin C contents were highest at the marketing stage (1,904 mg/g FW). Accumulations of Ca and K increased over cultivation time, whereas Zn contents were higher at the younger stages. However, Fe contents were not different by growth stages or varieties. From all measurements, only β-carotene and vitamin C accumulations were different among plant varieties. Compared to the WHO food recommendations, amaranths are excellent sources of β-carotene, antioxidants, calcium, potassium, and iron. Additionally, the associations among traits were evaluated and found that most traits were positively correlated with the growth stage, whereas zinc contents were strongly negatively correlated. These results provide a clear picture of amaranth’s nutrition for consumers and suggest the appropriate harvesting time for specific nutritional benefits as well as promoting the consumption of these vegetables.